The adjuvant use of capecitabine for residual disease following pre-operative chemotherapy for breast cancer: Challenges applying CREATE-X to a US population. (December 2021) - Beyerlin, Kassidy; Jimenez, Rachel; Zangardi, Mark; Fell, Geoffrey G; Edmonds, Christine; Johnson, Andrew; Bossuyt, Veerle; Specht, Michelle; Mulvey, Therese M; Moy, Beverly; Ellisen, Leif W; Isakoff, Steven J; et al.
Introduction: The CREATE-X study, conducted in Japan and South Korea, established capecitabine as an adjuvant treatment option for patients with triple negative breast cancer (TNBC) who have residual disease (RD) following neoadjuvant anthracycline or taxane-based chemotherapy. However, there are no reports on the tolerability and outcomes of adjuvant capecitabine in the US setting following publication of the CREATE-X data. Methods: We retrospectively collected treatment and tolerability data from the medical records of the first 23 TNBC patients who received adjuvant capecitabine for RD post neoadjuvant chemotherapy at our institution. Disease-free survival was assessed using the Kaplan-Meier method. Results: The median starting dosage of capecitabine was 1871 mg/m 2 /day, most commonly divided into two daily doses on days 1-14 of each 21 day cycle. 34.8% of patients completed the treatment as prescribed. Side effects associated with treatment were common with 69.6% of patients experiencing hand-foot syndrome, 39.1% of patients experiencing diarrhea, and 13.0% of patients requiring hospitalization for side effects. Of 23 patients treated with adjuvant capecitabine, 34.8% completed the planned dose, 30.4% completed with dose reduction, and 34.8% discontinued early. At a median follow-up time of 14 months, the median disease-free survival was 22 months, with 30.4% of patients experiencing recurrence. Conclusion: Tolerability was poor overall compared to the CREATE-X cohort. Administering adjuvant capecitabine for TNBC patients with residual disease in the United States is challenging given differences in tolerability. More research is needed to understand how poor tolerability will affect the efficacy of this approach in the US population.